SARS-CoV-2 Omicron variant shows less efficient replication and fusion activity when compared with Delta variant in TMPRSS2-expressed cells. Issue 1 (31st December 2022) - Zhao, Hanjun; Lu, Lu; Peng, Zheng; Chen, Lin-Lei; Meng, Xinjin; Zhang, Chuyuan; Ip, Jonathan Daniel; Chan, Wan-Mui; Chu, Allen Wing-Ho; Chan, Kwok-Hung; Jin, Dong-Yan; Chen, Honglin; et al.
ABSTRACT: The novel SARS-CoV-2 Omicron variant (B.1.1.529), first found in early November 2021, has sparked considerable global concern and it has >50 mutations, many of which are known to affect transmissibility or cause immune escape. In this study, we sought to investigate the virological characteristics of the Omicron variant and compared it with the Delta variant which has dominated the world since mid-2021. Omicron variant replicated more slowly than the Delta variant in transmembrane serine protease 2 (TMPRSS2)-overexpressing VeroE6 (VeroE6/TMPRSS2) cells. Notably, the Delta variant replicated well in Calu3 cell line which has robust TMPRSS2 expression, while the Omicron variant replicated poorly in this cell line. Competition assay showed that Delta variant outcompeted Omicron variant in VeroE6/TMPRSS2 and Calu3 cells. To confirm the difference in entry pathway between the Omicron and Delta variants, we assessed the antiviral effect of bafilomycin A1, chloroquine (inhibiting endocytic pathway), and camostat (inhibiting TMPRSS2 pathway). Camostat potently inhibited the Delta variant but not the Omicron variant, while bafilomycin A1 and chloroquine could inhibit both Omicron and Delta variants. Moreover, the Omicron variant also showed weaker cell–cell fusion activity when compared with Delta variant in VeroE6/TMPRSS2 cells. Collectively, our results suggest that Omicron variant infection is not enhanced by TMPRSS2 but is largely mediated via the endocytic pathway. The difference in entry pathway between Omicron and Delta variants may have an implication on the clinical manifestations or disease severity.